Reduced complexity M algorithm design for multiple symbol differential unitary space-time systems - Jin, Xiao-Ping; Ying, Ying-Guo; Jin, Ning (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2011)
To solve the problem of high complexity for multiple symbol differential detection(MSDD), a series of low complexity and sub-superior detect algorithms have been proposed so far, in which the M algorithm is well appreciated for its fixed complexity and latency. However the retained branches for each stage is assumed the same when the M algorithm is applied in the MSDD, but this method is not the best way in the view of complexity. In this paper, we propose a dynamic M algorithm in which the retained branches of each stage can be set to different value. The simulation analysis shows that the proposed algorithm not only reduce the number of branches from expanded and updated, but also has a better performance than constant M method in high SNR. In addition, the research on M algorithm focus on reducing the extended branches from the nodes to decrease the complexity, but the research on sort method of selecting M best paths is almost blank, so a low complexity sort algorithm is studied based on MSDD system. Anal